PEMBAGIAN PERAN DALAM RUMAH TANGGA PADA PASANGAN SUAMI ISTRI JAWA - Kusumaning Putri, Dyah Purbasari; Lestari, Sri (Jurnal Penelitian Humaniora, 2015)
The purpose of this study is to describe the division of roles of husband and wife in Javanese family. This study uses a phenomenological qualitative method. The subjects of this study consisted of six couples of Javanese residing in Surakarta. Data was collected using a semi-structured interview technique. Data analysis method used is descriptive analysis. The results showed that: (1) the couple shared a role in three areas namely decision-making, management of family finances, and parenting; (2) the process of the implementation of these roles is flexible; (3) The husband has a greater role in decision- making while wife in financial management and parenting. Efforts have always been made to maintain the harmony of the relationship as a partner in the implementation of these roles. It can be concluded that the philosophy of harmony remain the pillars of the guidelines in the relationship of married couples in the Javanese family.